DETERMINATION OF SECONDARY METABOLITE CONTENT, TOTAL PHENOLIC ANTIOXIDANT TEST, AND TOXICITY OF ULIN LEAF EXTRACT (Eusideroxylon zwageri Teijsm. & Binn) - Yayan Rabbani Kurniawan; adlis santoni; suryati suryati (LPPM, Institut Teknologi Sepuluh Nopember, 2022)
Ulin leaf (Eusideroxylon zwageri Teijsm. & Binn) is one of the traditional Indonesian medicinal plants. In this research, the secondary metabolite content, antioxidant activity, cytotoxic and total phenolic content were tested. The extraction process by maceration starts from hexane, ethyl acetate and methanol. The content of secondary metabolites of ironwood leaves are flavonoids, phenolics, steroids, terpenoids, and alkaloids. The results of the antioxidant activity test using the DPPH method (1,1-Diphenyl-2-Picrylhydrazil), methanol extract showed very strong activity IC50 10.96 mg/L, moderate ethyl acetate extract 115,409 mg/L and weak hexane extract IC50 368,555 mg/L. L. This result correlated with the total phenolic yield, methanol extract had the highest value of 162.95 mg GAE/Gram, followed by ethyl acetate extract of 96.7 mg GAE/Gram and hexane with a value of 19.85 mg GAE/Gram. The results of the cytotoxic test using the (BSLT) method on hexane extract had very strong toxicity LC50 82.1675 mg/L, methanol extract and weak ethyl acetate LC50, respectively; 683,282; and 812.456 mg/L.Key word : Ulin, Antioxidants, Total Phenolic, cytotoxic